Participatory research, people with intellectual disabilities and ethical approval: making reasonable adjustments to enable participation. Issue 3 (30th September 2014) - Northway, Ruth; Howarth, Joyce; Evans, Lynne
<x xml:space="preserve">Abstract</x> Aims and objectives The aim of this paper is to explore how making reasonable adjustments to the process of securing ethical approval for research can facilitate the meaningful involvement of people with intellectual disabilities as members of a research team. This is achieved through critical reflection upon the approach taken within one participatory research study whose objective was to explore how people with intellectual disabilities understand abuse. Background Internationally participatory research studies (in which active involvement of community members in all stages of the research process is sought) are becoming increasingly common in the context of health care and, more specifically, within research involving people with intellectual disabilities. However, whilst it is acknowledged that participatory research gives rise to specific ethical challenges, how (or if) involvement in securing ethical approval is facilitated, is not discussed in most research reports. The significance of this paper is that it seeks to address this gap by exploring how meaningful participation can be promoted by making reasonable adjustments. Methods Within the study, the research team worked in collaboration with the ethics committee to identify potential barriers that could prevent the participation of members of the research team who had intellectual disabilities. Reasonable adjustments (such as redesigning forms) were made to the processes involved in securing ethical approval. Conclusions This study demonstrated that it is possible to ensure that ethical standards are upheld and the requirements of ethics committees met whilst also facilitating the meaningful involvement of people with intellectual disabilities. Relevance to clinical practice The reasonable adjustments approach explored within this paper can be translated into the context of clinical practice: making changes to the way that services are delivered can promote greater involvement of people with intellectual disabilities in their own health care.